Political Conflicts in Hikayat Seri Kelantan from the Perspective of Theory of Conflict Behaviour - Idzwan, Faris; Jamian, Muhd Norizam (Malay Literature, 2024)
Hikayat Seri Kelantan (HSK) is one of Kelantan’s traditional Malay historiographical texts. As a historical literary text, this hikayat comprises various conflicts involving the Malay kingdom and its external powers. However, most studies on HSK focus more on the issue of war without discussing political conflicts as a whole. Therefore, this article discusses the political conflicts in HSK by outlining two objectives, which are to elaborate on the conflicts in HSK and to analyse the causes of the conflicts according to the theory of conflict behaviour. This article utilised the HSK manuscript edited by Mohd. Taib Osman (2004) as its primary source, while data collection was done using library research. Close reading strategy and analysis of descriptive text were applied in data analysis based on the theory of conflict behaviour by Bartos and Wehr (2002). The findings of this study showed nine events of political conflicts that could be categorised into four issues, which are: (1) the issue of tyrannical reign; (2) the issue of state sovereignty from external powers; (3) the issue of territorial expansion; and (4) the issue of position and power struggle in reign. The findings also revealed that disputes over resources comprising land or territory, power, and prestige are the premises for political conflicts in HSK. This study proves that HSK is a sociocultural document that has recorded various political conflicts of the Malay kingdom in Kelantan. Full text : PDF